2020
DOI: 10.1038/s41598-020-57664-w
|View full text |Cite
|
Sign up to set email alerts
|

YqfB protein from Escherichia coli: an atypical amidohydrolase active towards N4-acylcytosine derivatives

Abstract: Human activating signal cointegrator homology (ASCH) domain-containing proteins are widespread and diverse but, at present, the vast majority of those proteins have no function assigned to them. This study demonstrates that the 103-amino acid Escherichia coli protein YqfB, previously identified as hypothetical, is a unique ASCH domain-containing amidohydrolase responsible for the catabolism of N 4-acetylcytidine (ac4C). YqfB has several interesting and unique features: i) it is the smallest monomeric amidohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…and N 4 -(4-benzoyl-benzoyl)-2'-deoxycytidine were synthesised as described previously [58]. N 2 -acetylisocytosine and N 4 -acetyl-5-fluorocytosine were prepared as published previously [50].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…and N 4 -(4-benzoyl-benzoyl)-2'-deoxycytidine were synthesised as described previously [58]. N 2 -acetylisocytosine and N 4 -acetyl-5-fluorocytosine were prepared as published previously [50].…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence analysis using SMART [46] revealed that D8_RL contains the human activating signal cointegrator homology (ASCH) [47] and growth-arrest-specific protein 2 (GAS2) domains [48]. ASCH domain-containing proteins are widespread and diverse but, at present, the vast majority of those proteins have no function assigned to them [47], except for an ASCH domain-containing ribonuclease from Zymomonas mobilis [49] and a recently characterized unique ASCH domain-containing amidohydrolase YqfB from Escherichia coli, which is active towards N 4 -acylcytidines [50]. The comparison of YqfB and D8_RL amino acid sequences showed merely 17 identical residues between these two proteins, and only 2 of the 4 YqfB catalytic amino acids were among them, although the aspartic acid residue in position 72 of the D8_RL and the catalytic glutamic acid residue in position 74 of the YqfB enzyme can also be considered conservative ones (Figure 3 and Figure S2).…”
Section: Bioinformatic Analysis Of the Selected Clonesmentioning
confidence: 99%
See 3 more Smart Citations